دراسة تأثير مخلفات التبغ الجافة والمتخمرة كسماد عضوي في نمو وإنتاجية تبغ الفرجينيا صنف كوتساكا 51. - رقية, نزيه; سمرة, بديع; خضور, رامي (Latakia University Journal -Biological Sciences Series, 2019)
تعد عملية تدوير المخلفات الزراعية والصناعية في العصر الحديث من العمليات الهامة لحماية البيئة والاستفادة منها في عملية التسميد العضوي ولهذه الغاية تم إجراء تجربة في محطة بحوث تبغ كفريحمول- محافظة إدلب – فرع المنطقة الشمالية في المؤسسة العامة للتبغ، وذلك خلال الموسمين 2007 و2008 لدراسة إمكانية استخدام مخلفات التبغ المتخمرة بأنواعها الثلاثة (كسر ناعم – كسر خشن- بقايا سوق وأوراق جافة) بوصفها سماداً عضوياً نباتياً فقد أضيفت بمعدلين:1 طن و 2 طن/دونم من أجل دراسة تأثيرها في نمو وإنتاجية نبات التبغ صنف فرجينيا كوتساكا 51 Nicotiana tabacum. L(V K51) المزروع في تربة طينية، ومقارنتها بالسماد العضوي الحيواني و السماد الكيميائي، وقد بينت نتائج البحث:أن هناك إمكانية لاستخدام مخلفات التبغ بوصفها سماداً عضوياً إذ تم الحصول على أفضل النتائج في معاملة التسميد بمخلفات التبغ الناعمة بمعدل 2 طن/دونم مقارنة بمعاملات التسميد بمخلفات التبغ الأخرى، إلا أن نتائج معاملات التسميد الكيميائي والتسميد العضوي الحيواني أبدت تفوقاً بالمقارنة مع نتائج معاملات التسميد بمخلفات التبغ الجافة وبفروق إنتاجية. The recycling of the agronomic and industrial wastes has recently become an important procedure to protect the environment by utilizing them as an organic fertilizer. So, the experiment was carried out in the experimental tobacco station Kafar Yahmol, Idleb's province, a branch of the northern region of the General Organization of Tobacco during the two seasons of 2007 and 2008 to study the possibility of using the compost tobacco's wastes, which are of three kinds (small scrap residues, big scrap residues, and residues of dry stalks and leaves), as vegetal organic fertilizers at two rates of addition, 1 ton and 2 ton per 1000m2. And we study their effects on the growth and yield of flue-cured tobacco plant Nicotiana tabacum. L(VK51) cultivated in clay soil, in comparison with organic animal fertilization and mineral fertilization. Research outcomes indicated the possibility of using the compost tobacco's wastes as an organic fertilizer, for the best results were obtained through adding the small scrap wastes with rate 2 ton per 1000 m2 in comparison with other tobacco's waste treatments. But the results of each chemical fertilization and organic animal fertilization demonstrate predominance compared to the results of fertilization treatments by compost dry tobacco's wastes with differences of productivity.